Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0020480.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Biological Impacts of Climate Change

Abstract: Climate has far reaching impacts on biological systems. Survival and reproduction depend on how well adapted individuals are to local climate patterns. Climate change can disrupt the match between organisms and their local environment, reducing survival and reproduction and causing subsequent impacts on populations or species' distributions across geographic regions. Changes in climate may benefit some species and cause extinction for others. Cumulatively, it will alter biological communities and the functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Climate variation (rain fall, humidity, and temperature) formed part of the analysis of dengue fever trends as the dengue vector is very sensitive to climate change and the resulting environmental modifications. Since there is, to some extent, linear relationship between climate factors and the mutation process of the organisms (virus or bacteria) [ 13 ], we tried to correlate the climate information (Figures 4(a) – 4(c) ) with the incidence of disease from 2014 ( Figure 4(d) ). The study showed a strong and significant correlation with humidity and positive dengue cases ( p < 0.001) and also showed a significant correlation with low and medium rainfall ( p < 0.039).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate variation (rain fall, humidity, and temperature) formed part of the analysis of dengue fever trends as the dengue vector is very sensitive to climate change and the resulting environmental modifications. Since there is, to some extent, linear relationship between climate factors and the mutation process of the organisms (virus or bacteria) [ 13 ], we tried to correlate the climate information (Figures 4(a) – 4(c) ) with the incidence of disease from 2014 ( Figure 4(d) ). The study showed a strong and significant correlation with humidity and positive dengue cases ( p < 0.001) and also showed a significant correlation with low and medium rainfall ( p < 0.039).…”
Section: Resultsmentioning
confidence: 99%
“…McCarty et al reported “Climate change may benefit some species and cause extinction for others. Cumulatively, it will alter biological communities and the functioning of ecosystems” [ 13 ]. Results of similar studies also suggest a linear relationship with the incidence of dengue due to climate variations in Bangladesh by Karim et al [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Predicting the effects of global climate change on species interactions is one of the most pressing challenges for ecologists. Ectotherms are particularly sensitive towards thermal conditions and show severe declines in abundances in respond to climate change 1,20,81 . Whilst the major body of literature focused on rising mean temperatures to date, many studies neglected the increasing frequency of temperature variations and its intricated consequences on biotic interactions.…”
Section: Discussionmentioning
confidence: 99%